Influência do período de transporte pré-abate de bovinos nos níveis séricos de creatinoquinase, hemograma e pH final da carcaça - Silva, Maianne Borges da (2016)
This study aimed to evaluate the effects of road transport vehicles and step time in cattle before slaughter and determine serum creatinine, blood count and the carcass final pH. A total of 162 animals were used transported by three different periods to the slaughterhouse being classified according to the transport time being as short by step (for 31 min), medium (for 4 hours and 30 minutes) and long (for 18 hr and 20 min). Blood samples were taken loading, landing and bleeding. The average body weight of the animals was 580.4±11.6 kg in different periods of transport, demonstrating the standardization among the groups submitted to treatment, and the hot carcass weight did not differ at different times of transport, with average weight of 308.5±11.2 kg. The enzyme creatine kinase, there was no difference (P>0.05) among the different periods of transport, averaging 957.4UI. There was no difference (P>0.05) between the moments (loading, landing, bleeding), with means of 957.3 UI. The average values of erythrocytes in the short and medium period did not differ, averaging 9,55x106 / microl and as well, the mean hemoglobin levels did not differ in the short and medium periods, which showed 13.0 g/dl, (p≤0.05). Means of carcass temperature and final pH differed from that found after 45 minutes of slaughter (p=0.05). The initial pH was 6.86 and was 5.58 after 24 hours, and superficial temperature immediately after slaughter was 30,4oC and after 24 hours dropped to 4,13oC. However, the carcass final pH transported for long period was superior (p=0.05), with a value of 5.86. However, transport generates muscle damage to cattle, with an increase in creatine kinase enzyme in the blood, and also causes leukocytosis and neutrophilia due to the stress at pre-slaughter transport. Furthermore, this transportation over long periods above 18 hours, raises the carcass final pH.